FUZZY CLUSTERING MEANS (FCM) DALAM PENENTUAN LOKASI PENERTIBAN PENYAKIT MASYARAKAT PADA KEGIATAN PEMBINAAN SOSIAL SATPOL-PP WILAYAH SUMATRA-BARAT: Dine Tiara Kusuma; Rakhmadi Irfansyah Putra - Jurnal, Redaksi Tim (PETIR, 2018)
Based on the data summary disease community policing activities by municipal police pp city of West Sumatra in January 2010 to December 2014, there were as many as 1660 cases of approximately 20 locations enforcement. Each location policing there are various types of activities are classified as a disease of society. Based on data obtained are activities that have curbed such as street vendors, illegal buildings, street children, street, commercial sex workers (CSWs) and others. Number of activities at each point different locations each year, thus requiring data clustering method to facilitate the investigation team in determining the behavior patterns of disease activity as a description of the location community policing a priority next year. The method used in this data clustering method is to use Fuzzy Clustering Means (FCM)